Total control of chromium in tanneries - thermal decomposition of filtration cake from enzymatic hydrolysis of chrome shavings - Kocurek, P; Kolomazník, K; Bařinová, M; Hendrych, J (Waste management & research., 2017)
This paper deals with the problem of chromium recovery from chrome-tanned waste and thus with reducing the environmental impact of the leather industry. Chrome-tanned waste was transformed by alkaline enzymatic hydrolysis promoted by magnesium oxide into practically chromium-free, commercially applicable collagen hydrolysate and filtration cake containing a high portion of chromium. The crude and magnesium-deprived chromium cakes were subjected to a process of thermal decomposition at 650°C under oxygen-free conditions to reduce the amount of this waste and to study the effect of magnesium removal on the resulting products. Oxygen-free conditions were applied in order to prevent the oxidation of trivalent chromium into the hazardous hexavalent form. Thermal decomposition products from both crude and magnesium-deprived chrome cakes were characterized by high chromium content over 50%, which occurred as eskolaite (Cr2O3) and magnesiochromite (MgCr2O4) crystal phases, respectively. Thermal decomposition decreased the amount of chrome cake dry feed by 90%. Based on the performed experiments, a scheme for the total control of chromium in the leather industry was designed.
Keywords: Spectrometry, X-Ray Emission; Chromium; Industrial Waste; koželužství; Waste Management; nakládání s odpady; chrom; X-Ray Diffraction; spektrometrie rentgenová emisní; koncentrace vodíkových iontů; hydrolýza; difrakce rentgenového záření; Hydrogen-Ion Concentration; Tanning; průmyslový odpad; Hydrolysis